State of cutaneous microcirculation in patients with obesity - Andreieva, I. O.; Riznyk, O. I.; Myrnyi, S. P.; Surmylo, N. N.; Різник, Ольга Іванівна; Мирний, Сергій Петрович (Poland : ALUNA Publishing House, 2021)
ABSTRACT. The aim: To determine the influence of obesity on cutaneous microcirculation in patients with different stages of obesity and without cardio-vascular pathologies. Materials and methods: The 67 eligible patients with obesity were enrolled into the main group in this research. 20 healthy patients with normal body weight were included in the control group in this study. The mean age and gender were similar among the groups. Each patient underwent a clinical evaluation during the consultation, biological tests, electrocardiogram, Laser Doppler flowmetry. Results: There was a significant decrease in IM and σ in patients with class II obesity and class III obesity compared with control group. IV was decreased in all groups, but the significant differences were recorded only among patients with obesity and not among overweight patients. During wavelet analysis a significant decrease of the AmaxE was detected in all 4 groups (by 14,7%, 37,7%, 52,4%, 57,4% respectively, P < 0,05). The most significant changes were recorded in the heart spectrum (AmaxC). Conclusions: Overweight patients and patients with obesity without cardio-vascular pathology have initial manifestations of microcirculatory disorders, which deteriorate with an increase of BMI. Changes in microcirculation in patients with obesity characterized by the significant decrease of microvessels perfusion, decreasing endothelial and increasing heart specter modulations. Only high BMI was found to be associated with impaired microcirculation endothelial function (AmaxE B=0.446, 95% CI [0,15, 0,92] according to the results of regression analysis.
Keywords: obesity; microcirculation; overweight